Transfección de células por medio de ondas de choque - E. Armenta Ruiz (Revista Mexicana de Física, 2006)
Treatments for inherited and acquired diseases are pointing towards gene therapy, which depends on methods to introduce foreign geneticmaterial into cells. Unfortunately, most of the methods available to allow incorporation of transgenes into the genome are not selective totarget a particular population of cells. The present article describes the use of shock waves as a cell permeabilization method to load areporter gene into cultured cells. Shock waves were generated by underwater electrical breakdown and focused on the vials containing cellsuspension using an ellipsoidal reflector. Transfection was achieved due to acoustic cavitation generated inside the test vials after passageof each shock wave. The number of transfected cells was still low; nevertheless, our results show the feasibility of cell transfection byunderwater shock waves.